Short-Term Changes in Recorded Anxiety and Systolic Blood Pressure After a Dhikr-Based Relaxation Intervention in Cancer Patient - Andi Sulfikar; Andriana Arfah; Musdalipah; Syahrul Said; Titi Iswanti Afelya; Indah Restika BN; Ridwan (Innovative Approaches in Health Science Journal, 2026)
Background: Anxiety is common during cancer care, and spiritually congruent supportive interventions may be acceptable to patients who request them. Evidence from local implementation settings remains limited. Objective: To evaluate short-term changes in recorded anxiety severity and systolic blood pressure after a dhikr-based relaxation intervention among hospitalized adults with cancer. Methods: This evidence-based practice implementation project used a one-group pretest-posttest evaluation. Sixteen participants were recruited through a nonprobability consecutive approach between 4 and 26 November 2019. The intervention comprised two 15-minute sessions separated by a 30-minute rest period and combined guided slow breathing, relaxation, and Islamic dhikr. Anxiety and vital signs were assessed immediately before and after the intervention. Results: The recorded anxiety category score decreased from 2.31 (SD 0.79) to 1.44 (SD 1.03; p = 0.001). Mean systolic blood pressure decreased from 125.63 (SD 15.90) to 113.13 (SD 16.22) mmHg (p = 0.001). The archived pulse output contained no pretest or posttest descriptive values and was not interpreted. Conclusion: The combined dhikr, breathing, and relaxation intervention was associated with lower immediate postintervention anxiety category scores and systolic blood pressure. The small sample and absence of a control group preclude causal attribution.